Formulation and characterization of Halymenia dilatata-based nori alternative through nutritional, sensory, structural, textural, and functional analyses - C. E. Bridgete Princey; P. Ganesan; L. Vinoth Kumar; B. Sivaraman (Journal of Fisheries, 2026)
The increasing demand for seaweed-based foods has created interest in developing sustainable alternatives to conventional Porphyra-based nori using tropical seaweed resources. This study developed a nori-like product from Halymenia dilatata and evaluated the effects of glycerin concentration and drying conditions on its nutritional, physicochemical, structural, and sensory properties. Four formulations were prepared using a constant seaweed-to-water ratio (1:10, w/v) with varying glycerin concentrations. The formulation containing 2.5% glycerin and dried at 55°C for 2 h produced sheets with the best pliability, uniformity, and handling characteristics. The optimized product contained low moisture (7.84%), moderate protein (11.62%), high dietary fibre (31.54%), and a mineral-rich ash content (14.87%), with appreciable levels of iron and zinc and a balanced sodium-to-potassium ratio. Sensory evaluation indicated good consumer acceptance for appearance, flavour, texture, and overall acceptability. Structural analyses confirmed the formation of a cohesive polysaccharide network, while biochemical and microbiological analyses demonstrated favourable quality, oxidative stability, and microbial safety. These findings demonstrated that H. dilatata could be successfully developed into a nutritious, safe, and acceptable nori-like product with physicochemical characteristics comparable to those of conventional nori, highlighting its potential as a sustainable tropical alternative for value-added seaweed-based food products.